Status Anak Pasca Perceraian Nikah Siri dalam Hukum Positif dan Hukum Islam : Studi Kasus di Desa Burujukulon Kabupaten Majalengka - Eka; Rahayu, Hilma (El 'Ailaah, 2024)
A child's status will greatly influence their future, both in terms of income, guardianship, inheritance, and so on. In positive law, children resulting from unregistered marriages, if their parents divorce, cannot claim rights because they do not have legal legal protection. Meanwhile, in Islamic law, children have rights that must be fulfilled in all aspects, even if the child is the result of a registered marriage or the result of an unregistered unregistered marriage. This research aims to determine cases regarding the status of children after divorce in unregistered marriages in Burujulkulon village, Majalengka district, and to find out the comparison/comparison of reviews of Positive Law and Islamic Law regarding this matter. The research method used by researchers is qualitative research by combining two types of data, namely data obtained from field research in the form of observations, interviews and documentation in Burujulkulon village, Majalengka district. The basis/basis of legal sources used by researchers in the comparison process is positive law from the Law, Civil Code, and Government Regulations. Meanwhile, the Islamic law used comes from the Al-Qur'an, hadith, translated books and the opinions of the jurists. The data that researchers obtained was then reduced, presented and concluded using descriptive - comparative analysis techniques. Based on the research conducted, several conclusions were obtained including: (1) The status of the child which includes four things (recognition, education, livelihood and love, and lineage), in terms of livelihood and education in case A, the child from the unregistered marriage was not getting support from the father to the child, but in terms of recognition, the father admits that the child is his son. In contrast to case B, the child resulting from the unregistered marriage received support, education and recognition from his father; (2) in terms of recognition, education, living and affection in cases A and B, both of them fulfill and are sufficient for children's rights, this shows that there is conformity between the legal regulations that have been established, namely positive law and Islamic law; (3) there are differences in cases A and B, namely differences in registering the child's birth certificate, case A only lists the mother's name, and case B lists the names of both parents. This shows that there is a discrepancy between the legal regulations that have been established, namely positive law and Islamic law in terms of the child's lineage or population status.